Negotiating Audit Fees: Strategies for Achieving Fair and Equitable Pricing in Audit Engagements - Ahmad, Hamzah; Muslim, Muslim (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study explores the complexity of audit fee negotiations and their impact on audit quality and independence. The study also highlights factors influencing the negotiation process, such as client characteristics, industry dynamics, and regulatory requirements. Research Design and Methodology: This study applies a systematic approach to analyze and synthesize qualitative data from scholarly articles and other relevant sources related to audit fee negotiations. Findings and Discussion: The results show that client size, complexity, and industry competition are essential in determining audit fees. Auditors should customize fee structures based on client-specific needs and industry sector dynamics. In addition, transparency, communication, and trust-building are essential in creating constructive negotiations. This research also reveals the potential impact of fee negotiations on audit quality and independence. Findings and Discussion: This study's implications guide auditors, clients, regulators, and other stakeholders in effectively navigating the fee negotiation process. It aims to promote fairness, transparency, and integrity in the audit profession and maintain audit quality and independence. Implications: This study's implications guide auditors, clients, regulators, and other stakeholders in effectively navigating the fee negotiation process. It aims to promote fairness, transparency, and integrity in the audit profession and maintain audit quality and independence.